Opportunities to Improve Quality Outcomes: Integrating Nutrition Care Into Medicare Advantage to Address Malnutrition and Support Social Determinants of Health - Mary B. Arensberg RDN, PhD; Kaitlyn Saal-Ridpath JD, MPH; Kirk Kerr PhD; Wendy Phillips RDN, MS (SAGE Publishing, 2022)
Medicare Advantage (MA) is a public-private healthcare program for older adults and individuals with disabilities in the United States (US). MA enrollees receive their benefits from private health plans and the percentage of Medicare beneficiaries in MA plans continues to increase. MA plan enrollees typically have more socioeconomic risk factors compared to traditional Medicare enrollees. The COVID-19 pandemic has highlighted the importance of MA plans' flexibilities to address socioeconomic risk factors, or social determinants of health (SDOH), and to tailor benefits and services to meet individual MA enrollee needs. Poor nutrition-often termed malnutrition or protein calorie malnutrition-is a problem for many Medicare beneficiaries. Malnutrition can prolong recovery and increase medical complications and readmissions. Up to half of older Americans are at risk for malnutrition or are malnourished. Nutrition-related supplemental benefits offered by MA plans can most effectively help address malnutrition and impact SDOH and quality outcomes as part of multi-modal interventions. Multi-modal interventions integrate quality nutrition care throughout the MA care process. This Editorial explores the issue of older adult malnutrition and SDOH and the nutrition-related supplemental benefits currently offered by MA plans. It also identifies opportunities for further nutrition benefit development and impact, including through integration in MA outcome measurements and quality frameworks.